An ecological analysis of secondary school students' drug use in Hong Kong: A case-control study. (February 2016) - Tse, Samson; Zhu, Shimin; Yu, Chong Ho; Wong, Paul; Tsang, Sandra
Background: Youth drug use is a significant at-risk youth behaviour and remains as one of the top priorities for mental health services, researchers and policy planners. The ecological characteristics of secondary school students' behaviour in Hong Kong are understudied. Aim: To examine individual, familial, social and environmental correlates of drug use among secondary students in Hong Kong. Method: Data were extracted from a school survey with 3078 students. Among the 3078 students, 86 students reported to have used drugs in the past 6 months. A total of 86 age- and gender-matched controls with no drug-use behaviour in the past 6 months were randomly selected from the remaining students. Multiple logistic analysis was used to examine differential correlates between those who used and did not use substance in the past 6 months. Result: Positive school experience and perspective to school and parental support are protective factors of drug use. Lower self-esteem, lower self-efficacy against using drugs and higher level of permissive attitude towards drugs were associated with drug use. Students who were low in self-esteem and rather impulsive tend to use drugs. Conclusion: To prevent students from drug use, efforts in individual, family, school and community-levels should be addressed.